20 Mazindol effect on cerebral response to nonverbal affective vocalisation in healthy individuals: an fmri study. Issue 8 (13th July 2017) - Koeda, Michihiko; Ikeda, Yumiko; Tateno, Amane; Suzuki, Hidenori; Okubo, Yoshiro
Abstract : Background/Aims: Mazindol is known as one of the anorexiants for morbid obesity. According to previous study, the pharmacological property is similar to amphetamine, and this drug has an augmenting role of dopamine and serotonin by the inhibition of presynapse transporter. However, the neural basis of how mazindol acts on affective processing has been unclear. We investigated the cerebral response to nonverbal affective vocalisation to clarify the effect of mazindol by functional magnetic resonance imaging (fMRI). Methods: 20 healthy subjects (11 males, 9 females: mean age: 28.2 years, SD=6.4) participated in this study. The study protocol was approved by the ethics committee of Nippon Medical School, and all subjects provided their informed consent. This experiment was performed by randomised controlled trial. Each subject underwent two fMRI experiments, taking either a placebo or 0.5 mg of mazindol 2 hours before the scan. For each subject, the two experiments were separated by at least 2 weeks. Event-related fMRI experiments were performed in this study. The subjects listened to 3 types of emotional sounds: happy, sad, and neutral sounds. Each subject judged whether the emotional valence was positive, negative, or neutral. Data analysis was performed by statistical parametric mapping (SPM8). Results: As for fMRI accuracy, two-way repeated ANOVA (3 emotions×2 medications (placebo/mazindol)) showed no significant difference both in main effect of emotion (F (2, 76)=1.22, p>0.05), and in main effect of medication (placebo/mazindol: F (1, 38)=2.01, p>0.05). The fMRI experiment according to two-way repeated ANOVA showed significant difference both in main effect of emotion (F (2, 76)=60.7, p<0.001), and in main effect of medication (placebo/mazindol: F (1, 38)=11.82, p<0.001). In cerebral response, two-way repeated ANOVA showed significant difference in main effect of emotion at the bilateral superior temporal gyrus, and left prefrontal gyrus (p<0.001, uncorrected). In main effect of medication, significant activation was observed at the bilateral medial frontal cortex, bilateral putamen, left superior frontal gyrus, and anterior cingulate (p<0.001, uncorrected). Further interaction effect (emotion × medication) was observed at bilateral caudate (p<0.001, uncorrected). Conclusion: According to these results, cerebral function in vocal affective processing was changed by the action of madindol, especially in the area associated with dopaminergic neuron including medial frontal cortex and anterior cingulate.